Development of Iot Light Planning Assistant Technology for Smart Electrical System Simulation in Utilities Construction Drawing Learning Buildings at Private Vocational Schools of the Nias Regional Government - Resman Hendi Nofanolo Harefa; M. Giatman; Ambiyar; Dedy Irfan (Jurnal Penelitian Pendidikan IPA, 2025)
By utilizing IoT-based digital media such as iLPA, students are expected to be able to apply theory in real-world contexts that mimic real-world workplace conditions. This study aims: Develop IoT Light Planning Assistant (iLPA) learning media in the form of a relevant and contextual Smart Electrical System simulation. Type of research: This study uses a Research and Development (RnD) method with the aim of developing Internet of Things (IoT)-based learning media in the form of a Smart Electrical System simulation integrated into the Building Utility Construction Drawing course. The results showed that the validity aspect of the learning media achieved an average Aiken V-score of 0.88, indicating a valid category based on the assessment. All assessment aspects received Aiken V-scores above 0.75, with the ease of navigation of the IoT system and the quality of the comparison graphs with SNI 6197:2020 receiving the highest scores of 0.93. The practicality of the learning media demonstrated very satisfactory results, with an average score of 4.5 out of 5 (90%) based on responses from DPIB vocational teachers and an average score of 4.2 out of 5 (84%) based on student responses. The integration aspect with the DPIB curriculum received the highest rating from teachers (4.7/5), while the usefulness of the SNI 6197:2020 comparison feature received the highest rating from students (4.4/5).